Effectiveness of Progressive Mobilization on Functional and Hemodynamic Status in Bedrest Patients in the ICU: Randomized Controlled Trial - Dina Aryanti; Dudut Tanjung; Asrizal Asrizal (Jurnal Berita Ilmu Keperawatan, 2022)
Patients with health problems who undergo bed rest for a long time can experience various health problems. Problems that can be felt by patients on functional and hemodynamic status. This study aims to identify the effectiveness of progressive mobilization on functional status and hemodynamics in bed rest patients. The research method used a qualitative design with a randomized controlled trial method. The number of samples in this study was 70 people for each group. The sample in this study was taken by simple random sampling method with a total of 70 people in the control group and 70 people in the intervention group. Bivariate statistical test used Friedman and Mann Whitney test, while multivariate test used logistic regression. The results of this study showed that there was a significant effect of progressive mobilization on functional and hemodynamic status (p0.05). The conclusion of this study is that progressive mobilization is effective on the functional and hemodynamic status of the patient so that it can be applied in the ICU of the hospital as a nursing intervention